Flexural Behavior of Extruded DFRCC Panel and Reinforced Concrete Composite Slab - Chang-Geun Cho; Bang Yeon Lee; Yun Yong Kim; Byung-Chan Han; Seung-Jung Lee (Advances in Materials Science and Engineering)
This paper presents a new reinforced concrete (RC) composite slab system by applying an extruded Ductile Fiber Reinforced Cement Composite (DFRCC) panel. In the proposed composite slab system, the DFRCC panel, which has ribs to allow for complete composite action, is manufactured by extrusion process; then, the longitudinal and transverse reinforcements, both at the bottom and the top, are placed, and finally the topping concrete is placed. In order to investigate the flexural behavior of the proposed composite slab system, a series of bending tests was performed. From the test results, it was found that the extruded DFRCC panel has good deformation-hardening behavior under flexural loading conditions and that the developed composite slab system, applied with an extruded DFRCC panel, exhibits higher flexural performance compared to conventional RC slab system in terms of the stiffness, load-bearing capacity, ductility, and cracking control.